2016
DOI: 10.3389/fnmol.2016.00160
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Junction Impairment in Amyotrophic Lateral Sclerosis: Reassessing the Role of Acetylcholinesterase

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a highly debilitating disease caused by progressive degeneration of motorneurons (MNs). Due to the wide variety of genes and mutations identified in ALS, a highly varied etiology could ultimately converge to produce similar clinical symptoms. A major hypothesis in ALS research is the “distal axonopathy” with pathological changes occurring at the neuromuscular junction (NMJ), at very early stages of the disease, prior to MNs degeneration and onset of clinical symptoms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 107 publications
1
42
0
Order By: Relevance
“…Neuromuscular junction destruction is an early pathological change in SOD1‐G93A mice . We labeled NMJs on cross section of gastrocnemius muscle using α‐bungarotoxin.…”
Section: Resultsmentioning
confidence: 99%
“…Neuromuscular junction destruction is an early pathological change in SOD1‐G93A mice . We labeled NMJs on cross section of gastrocnemius muscle using α‐bungarotoxin.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence in ALS patients and murine models expressing ALS‐linked SOD1 mutations indicate that peripheral axons are lost before the death of cell bodies in the central nervous system (CNS; Fischer et al, ; Frey et al, ; Kennel, Finiels, Revah, & Mallet, ). Degeneration of motor axons in ALS has been associated with defective axonal transport, mitochondria function, and/or destabilization of neuromuscular junctions, among others (Arbour, Tremblay, Martineau, Julien, & Robitaille, ; Campanari, Garcia‐Ayllon, Ciura, Saez‐Valero, & Kabashi, ; Kong & Xu, ; Millecamps & Julien, ). The progressive loss of motor axons in ALS results in a Wallerian‐like degeneration characterized by axon fragmentation, the disintegration of the axonal cytoskeleton, myelin degradation, and immune cell infiltration (Chiu et al, ; Fischer & Glass, ), representing a stereotyped response to promote axonal growth and nerve repair.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that muscle weakness has an important role in ALS pathology, although it is not clear whether denervation originates from the motor neuron soma, or the muscle . Previous studies have shown that the exclusive expression of mutant SOD1G93A (mSOD1) in the skeletal muscles can lead to denervation of the neuromuscular junctions (NMJs), which lose the ability to regenerate and become atrophic, thus contributing to the symptoms of ALS . Indeed, several mechanisms implicated in the physiological maintenance of skeletal muscle are deregulated in ALS, such as satellite cell (SC) activity, mitochondrial and miRNA biogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…regenerate and become atrophic, thus contributing to the symptoms of ALS (7). Indeed, several mechanisms implicated in the physiological maintenance of skeletal muscle are deregulated in ALS, such as satellite cell (SC) activity, mitochondrial and miRNA biogenesis (17,18,31,41).…”
mentioning
confidence: 99%